Writing chemistry patents and intellectual property : a practical guide - Waller, Francis J. (Hoboken, NJ : Wiley, 2011)
"This book, based on a short course the author gives for the American Chemical Socitey, provides the necessary insights, strategies, and examples of how to write a patent so it is not rejected by the United States Patent and Trade Office (USPTO) or the patent does not have invalid claims"--
CHAPTER 9: AN EXAMINATION OF CLAIM FORMATCHAPTER 10: WHY YOU NEED CONFIDENTIALITY AGREEMENTS; CHAPTER 11: PRACTICAL INFORMATION ABOUT COPYRIGHTS AND TRADEMARKS; CHAPTER 12: GLOBAL PATENT FILING AND PATENTING STRATEGY; CHAPTER 13: WHAT ACADEMIC SCIENCE FACULTY SHOULD KNOW ABOUT PATENTS AND COPYRIGHTS; CHAPTER 14: INTELLECTUAL PROPERTY RESOURCES; CHAPTER 15: BOOK SUMMARY AND ON YOUR OWN; CHAPTER 16: RESPONSES TO QUESTIONS AT END OF CHAPTERS; CHAPTER 17: PATENT APPENDIX; INDEX
Includes bibliographical references and index.
Description based on print version record.
Keywords: Chemistry -- Patents; Intellectual property; Technical writing; SCIENCE / Chemistry / General; Chemistry -- Patents; Intellectual property; Technical writing; Electronic books; Electronic resource; Electronic books; Electronic books